Problematics Of Business And Management Education In Vocational Schools : Systematic Literature Review (SLR) - Siska Purwanti; Irvan Agung N; Nabila Amalia; Aniek Indrawati; Ludi Wishnu Wardana (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the problems of implementing business education in Vocational High Schools as an implementation of entrepreneurship at the Vocational High School level. This study uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that there was sufficient understanding of SMK students in the concept of business education, this was due to the existence of government programs that support and provide facilities for entrepreneurship learning in educational institutions, especially SMKs. In addition to this, the teaching staff also have skills in their fields, but it is still very unfortunate that not many teaching staff have their own business practices, so they are still based on books and other people's experiences. From this, it can motivate students to look for reference materials related to entrepreneurial knowledge and be able to see business opportunities well. Based on the analysis of the subject syllabus on entrepreneurship subjects, the material being taught is very much in line with current conditions and the expected competencies are clear. In addition, learning activities are project-based.